SYNTHESIS OF 2-(3'-HYDROXYBENZYLIDENE)CYCLOHEXANONE VIA CLAISEN-SCHMIDT REACTION BETWEEN 3-HYDROXYBENZALDEHYDE AND CYCLOHEXANONE USING MAOS METHOD - Asiah Nurul; Sri Handayani (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2017)
Synthesis of 2-(3'-hydroxybenzylidene)cyclohexanone via Claisen-Schmidt reaction between 3-hydroxybenzaldehyde and cyclohexanone used MAOS method has been done. The aim of this research was determined the yield of the 2-(3'-hydroxybenzylidene)cyclohexanone and identified the side product. 2-(3'-hydroxybenzylidene)cyclohexanone compound was sythesized through Claisen-Schmidt reaction between 3-hydroxybenzaldehyde and cyclohexanone. Synthesis of 2-(3'-hydroxybenzylidene)cyclohexanone used NaOH as catalyst by MAOS method for 500 seconds. The synthesis product were identified using TLC, TLC scanner, FTIR, and GCMS. Result of this research show that the yield of 2-(3'-hydroxybenzylidene)-cyclohexanone is 7.37%. The side product are 2-cyclohexylidenecyclohexanone and 2-(3'-hydroxy-benzylidene)-6-cyclohexylidenecyclohexanone.